Problem solving and social learning in spotted hyenas (Crocuta crocuta) - Kubina, Lindsay M. (Kansas State University, 2014)
Spotted hyenas (Crocuta crocuta) live in highly-complex, female-dominated groups called “clans.” Due to their social arrangement, spotted hyenas were a logical species on which to test the social complexity hypothesis. In the present study, they were presented with a series of puzzle boxes designed to test problem-solving behavior. The five puzzles varied in difficulty. All spotted hyenas solved the puzzle with the lowest difficulty level, five out of six solved the medium puzzles at least once, and one out of six solved the high difficulty puzzle. Some decreases in behavior diversity and time working on the puzzles were observed over successful trials; however, the decreases were only significant for successful trials of one medium-level puzzle. Decreases in work time were observed for some unsuccessful trials and the decrease was statistically significant for the highest difficulty puzzle. Overall, spotted hyenas were proficient at problem solving in the present study. Social learning is an important component of a lengthy juvenile period for spotted hyenas, and they have also been shown to influence one another’s feeding behavior. Furthermore, spotted hyenas participate in scramble competition when feeding and forage for and hoard food. In light of these behaviors, social learning was examined using the social transmission of a flavor preference (STFP) procedure. STFP was not observed overall. The sex of the subjects did not significantly influence the results; however, subjects that interacted with each other longer were significantly more likely to show STFP. The STFP procedure may not be sensitive enough to detect social learning in spotted hyenas. Perhaps spotted hyenas have no need to learn STFP due to their digestive and/or immune systems. The results of the current experiments make important contributions to existing knowledge. Data from other species like spotted hyenas are vital for evaluating the generality of the social complexity hypothesis since support thus far has come from data on primates. This study was the first to investigate STFP in a species from the Feliformia suborder. Additionally, finding more evidence that spotted hyenas have advanced cognitive abilities is essential for researchers and zoo personnel who work with spotted hyenas in captivity.
Keywords: spotted hyenas; problem solving; social learning; puzzle box; social transmission of a flavor preference; Psychobiology (0349); Psychology, Behavioral (0384); Zoology (0472)